Pengaruh Nilai Inti Perusahaan dan Implementasi Data Analytics Terhadap Pendeteksian Kecurangan pada Auditor Internal BUMN - Alwi, Mochamad; Winarningsih, Srihadi; Irawady, Cahya (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2024)
The purpose of this research is to analyze the influence of corporate core values and the implementation of data analytics towards fraud detection in partially and simultaneously. This research was conducted in Indonesia stated owned company. The independent variables in this research are the corporate's core values and the implementation of data analytics, while the dependent variable is fraud detection. The corporate’s core values analyzed is the corporate’s core values of Indonesia stated owned company namely akhlak core values which consist of trustworthy, competent, harmonious, loyal, adaptive and collaborative. The research subjects were internal auditors of IIA members who worked in Indonesia stated owned companies with experience as internal auditor for at least 5 years. This research uses quantitative method with descriptive analysis thru a survey approach with questionnaire distributed to respondents. The measurement scale in this research uses an ordinal scale to measure facts based on the respondent's experiences. The data analysis technique used in this research is multiple linear regression analysis. The population in this research were internal auditors of IIA member in Indonesia stated owned companies with experience as internal auditors for at least 5 years. The sample in this research used a simple random sampling method and the sample size used the Slovin formula. Based on the results of distributing the questionnaire, the selected sample was 118 respondents. The research results show that the corporate's core values and the implementation of data analytics have a significant and positive effect on fraud detection. The corporate's core values and the implementation of data analytics can contribute to fraud detection by 55.1%, while the remaining 44.9% is influenced by other factors that are not analyzed. Thus, implementing the corporate's core values along with implementing data analytics will increase fraud detection in Indonesia stated owned company